2016
DOI: 10.1155/2016/4374375
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as an Immunomodulating Adjuvant on T-Cells and Antigen-Presenting Cells in Herpes Simplex Virus Type 1 Infection

Abstract: Herpes disease caused by herpes simplex virus type 1 (HSV-1) is an intractable condition. It is a major concern in public health. Our purpose of this study was to verify the function of chitosan as an adjuvant for immune regulation specifically under herpes simplex virus type 1 (HSV-1) infection. Ahead of HSV infection, chitosan, heat inactivated green fluorescent protein expressing HSV (G-HSV), and a combination of chitosan and G-HSV were used to pretreat ICR mice followed by HSV-1 infection. Using flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
0
16
0
2
Order By: Relevance
“…−40.0 mV showed improved in vitro skin permeation and higher antiviral activity than the free drug against both the HSV-1 and the HSV-2 strains (Donalisio et al 2018). CS as an immunomodulating adjuvant on T cells and antigen-presenting cells in HSV-1 infected mice was reported by Choi et al (2016). In the dendritic cell-based DNA vaccine (pRSC-NLDC145.gD-IL21) carried by CS NPs, the expressed glycoprotein D in the formulation effectively targeted corneal dendritic cells and significantly alleviated the symptoms of both primary and recurrent HSV keratitis in mice via eliciting strong humoral and cellular immune response suggesting that such vaccine could be successfully used in Herpes simplex keratitis treatment (Tang et al 2018).…”
Section: Herpes Simplex Virusmentioning
confidence: 94%
“…−40.0 mV showed improved in vitro skin permeation and higher antiviral activity than the free drug against both the HSV-1 and the HSV-2 strains (Donalisio et al 2018). CS as an immunomodulating adjuvant on T cells and antigen-presenting cells in HSV-1 infected mice was reported by Choi et al (2016). In the dendritic cell-based DNA vaccine (pRSC-NLDC145.gD-IL21) carried by CS NPs, the expressed glycoprotein D in the formulation effectively targeted corneal dendritic cells and significantly alleviated the symptoms of both primary and recurrent HSV keratitis in mice via eliciting strong humoral and cellular immune response suggesting that such vaccine could be successfully used in Herpes simplex keratitis treatment (Tang et al 2018).…”
Section: Herpes Simplex Virusmentioning
confidence: 94%
“…Moreover, chitosan derivatives have shown their adjuvant activities such as activation of peritoneal macrophages, suppression of tumor growth and protection of the host against bacterial infection in mice and guinea-pigs [ 87 , 88 ]. Similarly, chitosan has significantly elevated the number of T cells, dendritic cells and natural killer cells in herpes simplex virus (HSV) infected mice [ 139 ]. Further, the adjuvant function of chitosan was compared with a standard vaccine adjuvant, cholera toxin (CT), in a study of vaccine delivery in mice infected with Helicobacter pylori [ 140 ].…”
Section: Needle-free Immunization With Chitosan Systemsmentioning
confidence: 99%
“…Oral administration of pCIN-mIL-4 DNA vector in combination with chitosan has effectively delivered DNA vector to intestinal tissues of mice. Our recent study has shown that chitosan itself can be a potential immune modulator [ 48 ]. Oral administration of chitosan significantly up-regulated frequencies of DX5+ natural killer cell populations in peripheral blood leukocytes (PBL).…”
Section: Therapeutic Applications Of Inflammatory Mice Model Of Bementioning
confidence: 99%
“…In HSV-infected mice, chitosan increased the frequencies of CD4+ T cells, CD8+ T cells, and CD11c+ dendritic cells in PBL. In addition, chitosan treatment down-regulated the levels of anti-HSV antibodies in the serum of HSV-infected mice, compared to the control group [ 48 ]. Thus, chitosan can be used as an adjuvant for gene delivery and an immune modulator by oral administration.…”
Section: Therapeutic Applications Of Inflammatory Mice Model Of Bementioning
confidence: 99%